Analisis Rantai Pasokan Tanaman Rimpang Terhadap Jumlah Produksi Produk Herbal Di Muara Teweh - Izzah, Zulfa Nur; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Muara Teweh is a location that has the potential for businesses to establish and develop their businesses. The extent of land and also its competitors which are still very minimal can be an opportunity for business actors. This opportunity is utilized as a location for cultivation such as rhizome plants as well as a source of raw materials. If managed properly, the results of the cultivation of these rhizome plants can become raw materials for the supply chain. This study aims to determine and analyze the supply chain of rhizome plants to the amount of herbal product production in Muara Teweh. The research method used is descriptive method using a quantitative approach. The results of the study show that the efforts and effectiveness in the supply chain are not optimal and affect the production target is not achieved.